Collective Action and Radicalism in Brazil : Women, Urban Housing and Rural Movements - Duquette, Michel, 1947- (Book collections on Project MUSE., 2005)
In the past decade, Brazil has undergone a long series of political changes, culminating in the recent election of President Lula da Silva and his Workers' Party. These changes have come about through a landslide of social activism that is unprecedented in the country's history. The central topic of this book is an examination of three major recent movements within Brazil's civil society: the women's movement, the urban housing movement, and the landless peasant movement. All three are representative of a more general trend toward public protest and collectively indicate a shift in the internal dynamics of group identity within Brazil. The authors propose that the practices of power in Brazil are influenced by the expressions of a civil society now reorganized into a social movement and mobilized within a 'cycle of protest' that attains the level of a political alternative and that the present cycle of collective action is fuelled by the pitfalls of market reforms.